Analisis Penetuan Harga Pokok Produksi untuk Menentukan Harga Jual Produk : Studi Kasus pada Akar Coffe - Alamsa Alamsa; Iqrima Mas Mappangile; Olivia Pamilangan Andi’lolo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the determination of the cost of production at the Akar coffe Shop to determine the optimal product selling price. In facing intense competition in the coffe industry, determining the right selling price is very important for business continuity. The research method used is mix method approach with production cost analysis, which includes raw material, labor and overhead costs. The findings of the study indicate There is a difference in the calculations according to the simple approach and full costing which affects the selling price.This research emphasizes the importance of accuracy in pricing to maintain a balance between costs and profitability.